2013
DOI: 10.1038/nri3552
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis-induced immunosuppression: from cellular dysfunctions to immunotherapy

Abstract: Sepsis — severe life-threatening infection with organ dysfunction — initiates a complex interplay of host pro- and anti-inflammatory processes. In a real sense, sepsis can be considered a race to the death between the pathogens and the host immune system. It is the proper balance between the often competing pro- and anti-inflammatory pathways that determines the fate of the individual. Although the field of sepsis research has witnessed the failure of many highly-touted clinical trials, a better understanding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

48
2,062
4
49

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 2,002 publications
(2,163 citation statements)
references
References 169 publications
48
2,062
4
49
Order By: Relevance
“…Prior Ultrasound Treatment Reduces Severity of AKI in Sepsis A critical issue in sepsis is the pathologic dysregulated response to bacterial infection leading to a hyperinflammatory cytokine storm response, 18 and the lack of homeostasis from dysfunction of the neuroendocrine and immune systems leads to multiorgan dysfunction and early death. 19 Using the cecal ligation puncture (CLP) model of sepsis, 20 the rise in plasma creatinine ( Figure 10A) and circulating cytokines (Table 2) in WT mice subjected to CLP was reduced significantly by pretreatment with ultrasound.…”
Section: Ultrasound Modulates Splenocytementioning
confidence: 99%
“…Prior Ultrasound Treatment Reduces Severity of AKI in Sepsis A critical issue in sepsis is the pathologic dysregulated response to bacterial infection leading to a hyperinflammatory cytokine storm response, 18 and the lack of homeostasis from dysfunction of the neuroendocrine and immune systems leads to multiorgan dysfunction and early death. 19 Using the cecal ligation puncture (CLP) model of sepsis, 20 the rise in plasma creatinine ( Figure 10A) and circulating cytokines (Table 2) in WT mice subjected to CLP was reduced significantly by pretreatment with ultrasound.…”
Section: Ultrasound Modulates Splenocytementioning
confidence: 99%
“…Pro-and anti-inflammatory stages of the host immune response to sepsis often occur concurrently (Hotchkiss et al 2013). Researchers have sought to identify biomarkers to distinguish or predict high-risk patients.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the HLA-DR level in patients with better outcomes of sepsis recovers in 1 week after administration. 6,23 Infection may be aggravated or uncontrolled in patients with immunosuppression, sometimes even causing death. 24 Meisel et al 20 and Schefold et al 25 demonstrated that awareness of the levels of mHLA-DR may help in guiding immunomodulatory therapy, shortening mechanical ventilation time and the duration of hospital stay.…”
Section: Discussionmentioning
confidence: 99%